Exploring the dark side of organizational citizenship behavior - Bolino, Mark C.; Klotz, Anthony C.; Turnley, William H.; Harvey, Jaron (Journal of organizational behavior, 2013)
In recent years, there has been increasing interest in positive organizational scholarship in general, including positive organizational behavior (POB) in particular. This work identifies organizational citizenship behavior (OCB) as a prototypical POB. Conceptualizing OCBs in this way is sensible in light of more than 30 years of research highlighting the desirable aspects of such behavior. At the same time, some researchers have raised questions about positive organizational scholarship and have called for a more balanced view of ostensibly positive behaviors. The purpose of this paper, then, is to take a more nuanced view of OCBs while highlighting the dark side of citizenship behavior. In doing so, we review conceptual and empirical work that has challenged the idea that OCBs are inherently positive. We also discuss research that seeks to develop a deeper understanding of the conditions under which OCB does more harm than good. Finally, important areas for future research and the practical realities facing scholars who seek to publish research investigating the dark side of citizenship are addressed as well.